The effect of electrophoretic deposition of carbon nanotubes on carbon fiber on interfacial properties of the thermoplastic polyimide composite - Jian, Li (Surface and interface analysis, 2024)
In order to improve the interfacial properties of carbon fiber/polyimide (CF/PI) composite, silanization reaction carbon nanotubes (CNTs) were introduced to the surface of carbon fiber by electrophoretic deposition to prepare CF/CNT/PI composite. The effects of carbon fiber surface treatment on the mechanical properties of the composites were studied. The results showed that the interlaminar shear strength and bending strength of the composite materials were increased by 11% and 9%, respectively. The scanning electron microscope and Atomic Force Microscope (AFM) was used to analyze the fine structure of composite interface phase. The results show that the introduction of CNTs creates an interface transition layer of CNTs reinforced PI resin between the fiber and the matrix.